Intramuscular Progesterone Optimizes Live Birth From Programmed Frozen Embryo Transfer: A Randomized Clinical Trial. Issue 12 (December 2021) - Devine, Kate; Richter, Kevin S.; Jahandideh, Samad; Widra, Eric A.; McKeeby, Jeffrey L.
Abstract : (Abstracted from Fertil Steril 2021;116:633–643) Approximately one third of assisted reproductive cycles in the United States are classified as frozen embryo transfer (FET). Given the widespread utilization of FET in the treatment of infertility, identifying endometrial preparation protocols that optimize live birth is critical.